2014
DOI: 10.1002/ejic.201400093
|View full text |Cite
|
Sign up to set email alerts
|

Mixed‐Valence Biferrocenium Salts of Xn–TCNQ (X = F, Cl; n = 1, 2): Correlation between Molecular Structures and Assembled Structures

Abstract: Charge‐transfer salts composed of biferrocene derivatives and Xn–TCNQ (X = F, Cl; n = 1, 2; TCNQ = tetracyanoquinodimethane) were prepared and crystallographically characterized. All nine salts exhibited a 1:2 donor/acceptor (D/A) ratio consisting of mixed‐valence biferrocenium cations and anions with acceptor dimers. The packing patterns were correlated to the donor substituents. On the basis of the π–π interactions of the cations, the observed structures were classified into three categories: segregated‐stac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 47 publications
(30 reference statements)
0
7
0
Order By: Relevance
“…Among them, the crystal structures and valence states of 1b, 1c, and 1d were reported previously. 9 The structure determination revealed that all of the salts were isomorphous with a 1:2 D/A ratio. 10 The packing diagrams of 3a and 3c are shown in Fig.…”
Section: Acceptor Charge Cmentioning
confidence: 97%
“…Among them, the crystal structures and valence states of 1b, 1c, and 1d were reported previously. 9 The structure determination revealed that all of the salts were isomorphous with a 1:2 D/A ratio. 10 The packing diagrams of 3a and 3c are shown in Fig.…”
Section: Acceptor Charge Cmentioning
confidence: 97%
“…Salt 6 was a dichloromethane solvate, which is the sole example of a solvate crystal for biferrocenium–TCNQ salts. The donor–acceptor ratios and valence states (I, monovalent; II, divalent) of 1 – 6 and related salts ,, are summarized in Table . Half of the salts are newly synthesized in the current study.…”
Section: Resultsmentioning
confidence: 99%
“…We have previously investigated the crystal structures and valence states of biferrocenium salts with tetracyanoquinodimethane (TCNQ) and other organic acceptors, and found that these salts exhibit intriguing electronic properties and phase transition phenomena. These salts generally exist in 1:1–1:3 D/A ratios, and their crystal structures can be classified into mixed-stack structures with alternating donor/acceptor stacking, segregated-stack structures with independent columnar π–π stacking of donors and acceptors, or an intermediate type (Figure a). ,, However, unlike organic charge-transfer complexes, there are often π–π contacts between the acceptors (or acceptor dimers) even in mixed-stack structures because of the nonplanar shape of the donor. Biferrocenium–TCNQ salts exhibit either monovalent state ([D] + [A m ] − ; m = 1–3) or divalent state ([D] 2+ [A m ] 2– ) (Figure b), depending on the balance between the redox potentials of the constituent molecules and the Coulombic (Madelung) energies of the crystal. The Madelung energies depend on the charges, volumes, and arrangements of the constituent molecules. There are also a few biferrocenium–TCNQ salts that contain both [D] + and [D] 2+ . , A phase boundary between the monovalent and divalent salts has been determined for the mixed-stack 1:2 D/A structures (Figure ).…”
Section: Introductionmentioning
confidence: 99%
“…The large neopentyl substituent in 1 prevents columnar stacking of the cations, whereas the tendency of unsubstituted biferrocene to form columnar structures has also been observed in other salts. 16,17 The packing structures of 3 and 4 were complicated.…”
Section: ■ Introductionmentioning
confidence: 99%